Effects of Reward and Punishment on Employee Performance in East Java Companies - Klemens Mere; Endang Sungkawati (Goodwood Publishing, 2026)
Purpose: This study synthesizes empirical evidence on how reward and punishment systems relate to employee performance in firms and MSMEs operating in East Java, Indonesia, and identifies the conditions under which these HRM mechanisms are most effective. Methodology: A PRISMA-guided systematic literature review searched Google Scholar, Garuda, SINTA-indexed journals, and university repositories for 2020–2025 studies focused on East Java business entities and the variables reward, punishment, and employee performance. Eligible full-text empirical studies were quality-appraised and synthesized using narrative synthesis. Results: Rewards improve performance when criteria are clear, measurable, and perceived as fair, aligning with expectancy and organizational justice. Punishment enhances discipline when sanctions are graded, proportional, and consistently enforced. However, reward effects weaken with ambiguous indicators or discretionary distribution, while punishment may backfire under stress or perceived injustice, creating fear and undermining motivation. The effectiveness of both systems depends on clear, consistent, and fair implementation. Conclusions: This PRISMA-guided review of studies from East Java (2020–2025) shows that reward and punishment systems improve employee performance based on clear indicators, consistency, and fairness, with rewards boosting motivation and punishments ensuring discipline. It provides regional insights on their effectiveness in East Java Limitations: The evidence base is dominated by cross-sectional, self-reported surveys and firm- or sector-specific samples, limiting causal inference and generalizability. Heterogeneous measures constraining quantitative pooling. Contributions: This review consolidates scattered findings from East Java, maps recurring patterns and boundary conditions, and provides context-sensitive implications for strengthening HRM and performance management.